Magnetic paste
Patent Information
- Application Number
- JP2024220570
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-02-18
AI Technical Summary
【0010】 本発明によれば、比透磁率が高い硬化物を得ることができる、粘度が低い磁性ペースト、及び当該磁性ペーストを使用した回路基板、インダクタ基板、並びにインダクタ基板の製造方法を提供することができる。
Smart Images

Figure 2025031745000016 
Figure 2025031745000017 
Figure 2025031745000018
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic paste, a circuit board using the magnetic paste, an inductor board, and a method for manufacturing a circuit board. [Background technology]
[0002] An inductor substrate that can be included in a circuit board such as a printed wiring board is formed by processing the resin composition containing the magnetic powder using a printing method, a pressing method, or the like, and the pressing method is one of the methods for improving the performance of the inductor substrate, since it can highly pack the magnetic powder.
[0003] The pressing method includes the WIP method, the CIP method, the compression molding method, etc. Among them, the compression molding method is capable of large-area processing and of forming an inductor substrate directly on the upper surface of a substrate.
[0004] Patent Documents 1 and 2, for example, describe magnetic resin compositions that can be formed by compression molding. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-199896 A [Patent Document 2] JP 2019-210447 A Summary of the Invention [Problem to be solved by the invention]
[0006] The magnetic resin composition described in Patent Document 1 is produced by kneading a solid resin in a kneader, so it has a high viscosity and the productivity of inductor substrates is poor. Also, the magnetic resin composition described in Patent Document 2 is intended for EMI shielding, so its applicable frequency band and relative permeability are not suitable for use in inductor substrates.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a low-viscosity magnetic paste that can give a hardened product with high relative magnetic permeability, as well as a circuit board, an inductor board, and a method for manufacturing a circuit board that use the magnetic paste. [Means for solving the problem]
[0008] As a result of intensive research into achieving the above-mentioned object, the inventors discovered that by adding a specific liquid epoxy resin, the viscosity of the paste can be reduced and the relative permeability of the cured product can be increased, thereby completing the present invention.
[0009] That is, the present invention includes the following. [1] (A) Magnetic powder, and (B) A magnetic paste for forming an inductor substrate using a compression mold, comprising a liquid epoxy resin represented by the following general formula (1): [ka] (In general formula (1), R represents a hydrogen atom or a methyl group.) [2] The magnetic paste according to [1], which has a relative permeability of 5 or more at a frequency of 10 MHz. [3] A magnetic paste according to [1] or [2], having a magnetic loss of 0.1 or less at a frequency of 10 MHz. [4] The magnetic paste according to any one of [1] to [3], having a viscosity at 0.5 rpm at 25°C of 30 Pa·s or more and 600 Pa·s or less. [5] The magnetic paste according to any one of [1] to [4], wherein R in general formula (1) represents a methyl group. [6] A circuit board comprising a magnetic layer formed from a cured product of the magnetic paste according to any one of [1] to [5]. [7] An inductor substrate comprising the circuit board according to [6]. [8] A method for manufacturing a circuit board, comprising the steps of supplying the magnetic paste according to any one of [1] to [5] onto an inner layer substrate, and molding the magnetic paste using a compression mold to form a magnetic layer. Effect of the Invention
[0010] According to the present invention, it is possible to provide a low-viscosity magnetic paste that can give a cured product with high relative magnetic permeability, as well as a circuit board, an inductor board, and a method for manufacturing an inductor board that use the magnetic paste. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view for explaining an example of an inner layer substrate. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating step (A) included in an example of a method for producing a circuit board. [Diagram 3] FIG. 3 is a schematic cross-sectional view illustrating step (A) included in an example of a method for producing a circuit board. [Figure 4] FIG. 4 is a schematic cross-sectional view illustrating step (B) included in the example of the method for producing a circuit board. [Diagram 5] FIG. 5 is a schematic cross-sectional view illustrating step (D) included in the example of the method for producing a circuit board. [Figure 6] FIG. 6 is a schematic plan view of an inductor substrate including a circuit board obtained by an example of a method for manufacturing a circuit board, as viewed from one side in the thickness direction. [Figure 7] FIG. 7 is a schematic diagram showing a cut end surface of an inductor substrate including a circuit board obtained by a method for manufacturing a circuit board cut at the position indicated by the dashed line II-II in FIG. 5 as an example. [Figure 8]FIG. 8 is a schematic plan view illustrating the configuration of a first conductor layer in an inductor substrate including a circuit board obtained by an example method for manufacturing a circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Each drawing merely shows the shape, size, and arrangement of components in a schematic manner to the extent that the invention can be understood. The present invention is not limited by the following description, and each component can be modified as appropriate. In the drawings used in the following description, similar components are indicated by the same reference numerals, and duplicated descriptions may be omitted. Furthermore, the configuration according to the embodiment of the present invention is not necessarily manufactured or used according to the arrangement of the illustrated example.
[0013] [Magnetic paste] The magnetic paste of the present invention contains (A) a magnetic powder and (B) a liquid epoxy resin represented by the following general formula (1). The magnetic paste of the present invention is used for forming an inductor substrate using a compression mold. [ka] (In general formula (1), R represents a hydrogen atom or a methyl group.)
[0014] In the present invention, by including component (B), the viscosity of the magnetic paste can be reduced, improving the productivity of the inductor substrate, and the hardened product of the magnetic paste can have an improved relative permeability at a frequency of 10 MHz. Also, preferably, the hardened product can have a reduced magnetic loss and improved mechanical properties.
[0015] The magnetic paste may further contain (C) a dispersant, (D) a hardener, and (E) other additives, as necessary. Each component contained in the magnetic paste of the present invention will be described in detail below.
[0016] <(A) Magnetic powder> The magnetic paste contains (A) magnetic powder as component (A). From the viewpoint of enabling both improvement of the relative magnetic permeability of the hardened product of the magnetic paste and reduction of magnetic loss, the (A) magnetic powder is preferably either a nanocrystalline magnetic material or an amorphous magnetic material, and from the viewpoint of enabling reduction of magnetic loss by reducing the magnetic anisotropy of the crystals, it is more preferable that the (A) magnetic powder contains a nanocrystalline magnetic material and an amorphous magnetic material. In this specification, the nanocrystalline magnetic material refers to a magnetic material containing crystal grains, and the grain size of the crystal grains of the magnetic powder is 100 nm or less. The nanocrystalline magnetic material preferably refers to a material having a maximum grain size of 100 nm or less. Usually, one particle of the (A) magnetic powder contains multiple crystal grains, and the grains can be polycrystalline. The size of the crystal grains can be observed, for example, by a TEM (transmission electron microscope). Since the nanocrystalline magnetic material contains crystal grains, it can usually show a peak indicating crystallinity in an X-ray diffraction pattern. Moreover, an amorphous magnetic material is a non-crystalline magnetic material that does not show a specific peak indicating crystallinity in the X-ray diffraction pattern. Usually, the X-ray diffraction pattern of an amorphous magnetic material shows a broad pattern without a peak indicating crystallinity. (A) By using either a nanocrystalline magnetic material or an amorphous magnetic material as the magnetic powder, the magnetic flux density is increased, and as a result, it is believed that it is possible to effectively achieve both an improvement in the relative permeability and a reduction in magnetic loss.
[0017] The (A) magnetic powder may be either a soft magnetic powder or a hard magnetic powder, but from the viewpoint of suppressing uneven distribution of the magnetic powder, a soft magnetic powder is preferable.
[0018] (A) Examples of the magnetic powder include iron alloy metal powders (Fe-based metal powders) such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Cr-Si alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, and Fe-Ni-Co alloy powder.
[0019] Among them, the (A) magnetic powder is preferably an iron alloy metal powder from the viewpoint of obtaining the effect of the present invention remarkably. The iron alloy metal powder preferably contains at least one selected from Fe, Si, Cr, Al, Ni, and Co, and more preferably contains an iron alloy metal powder containing Fe, Si, and Cr. In addition, it is more preferable that the magnetic powder is either a nanocrystalline magnetic material or an amorphous magnetic material containing at least one selected from Fe, Si, Cr, Al, Ni, and Co, and it is even more preferable that the magnetic powder is either a nanocrystalline magnetic material or an amorphous magnetic material containing Fe, Si, and Cr, and it is preferably either an Fe-based nanocrystalline magnetic material or an Fe-based amorphous magnetic material, and it is more preferable that the magnetic powder is an Fe-based nanocrystalline magnetic material. Here, the Fe-based means that the magnetic powder contains Fe atoms.
[0020] The magnetic powder (A) can be adjusted to a desired particle size distribution, for example, by classification. The above particle size distribution represents the particle size distribution of the entire component (A) contained in the magnetic paste. Therefore, the component (A) formed by mixing two or more types of magnetic powder may be adjusted to have a desired particle size distribution, or, for example, multiple magnetic powders not having the desired particle size distribution may be mixed so that the entire component (A) has the desired particle size distribution.
[0021] (A) The particle size distribution of magnetic powder can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of magnetic powder is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample is preferably a magnetic powder dispersed in pure water using ultrasonic waves. Examples of laser diffraction / scattering type particle size distribution measuring devices that can be used include Microtrackbell's "MT3000II," Horiba's "LA-960," and Shimadzu's "SALD-2200."
[0022] (A) The magnetic powder may be used alone or in combination of two or more kinds, but from the viewpoint of obtaining the effect of the present invention remarkably, it is preferable to use two or more kinds of magnetic powders in combination, and it is more preferable to use two or more kinds of magnetic powders with different average particle sizes in combination. In one embodiment, when two kinds of magnetic powders with different average particle sizes are used in combination, the average particle size of one magnetic powder is preferably 0.01 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. It is also preferably less than 10 μm, more preferably 9 μm or less, and even more preferably 8 μm or less. The average particle size of the other magnetic powder is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. It is also preferably 40 μm or less, more preferably 35 μm or less, and even more preferably 30 μm or less.
[0023] In the case of using two or more kinds of magnetic powders with different average particle sizes in combination, where the average particle size of one magnetic powder is a1 and the average particle size of the other magnetic powder is a2, a1 / a2 is preferably 1 or more, more preferably 3 or more, and even more preferably 5 or more, and is preferably 20 or less, more preferably 15 or less, and even more preferably 10 or less, with the proviso that a1>a2. By adjusting a1 / a2 to be within this range, the effects of the present invention can be obtained significantly.
[0024] As the (A) magnetic powder, commercially available products can be used, and two or more types may be used in combination. Specific examples of commercially available magnetic powders that can be used include "KUAMET NC1" and "ATFINE NC1" (nanocrystalline magnetic materials) manufactured by Epson Atmix, and "KUAMET 6B2" and "AW02-08PF3F" (amorphous magnetic materials) manufactured by Epson Atmix.
[0025] (A) The magnetic powder is preferably spherical. The value (aspect ratio) obtained by dividing the length of the long axis of the magnetic powder by the length of the short axis is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1.2 or less, and is preferably more than 1, more preferably 1.05 or more. In general, it is easier to improve the relative magnetic permeability when the magnetic powder is flat rather than spherical, but in the present invention, it is preferable to use spherical magnetic powder from the viewpoint of reducing magnetic loss and obtaining magnetism with a preferable viscosity.
[0026] (A) The specific surface area of the magnetic powder is preferably 0.05 m from the viewpoint of improving the relative magnetic permeability. 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more. Also, preferably 15m 2 / g or less, more preferably 12m 2 / g or less, more preferably 10m 2 / g or less. (A) The specific surface area of the magnetic powder can be measured by the BET method.
[0027] From the viewpoint of improving the relative magnetic permeability and reducing the loss factor, the content (volume %) of the (A) magnetic powder is preferably 40% by volume or more, more preferably 50% by volume or more, and even more preferably 60% by volume or more, when the non-volatile components in the magnetic paste are taken as 100% by volume, and is preferably 95% by volume or less, more preferably 90% by volume or less, and even more preferably 80% by volume or less.
[0028] From the viewpoint of improving the relative magnetic permeability and reducing the loss factor, the content (mass%) of the (A) magnetic powder is preferably 70 mass% or more, more preferably 75 mass% or more, and even more preferably 80 mass% or more, when the non-volatile components in the magnetic paste are taken as 100 mass%, and is preferably 99 mass% or less, more preferably 98 mass% or less, and even more preferably 97 mass% or less. In the present invention, the content of each component in the magnetic paste is a value when the non-volatile components in the magnetic paste are taken as 100 mass %, unless otherwise specified.
[0029] <(B) Liquid epoxy resin represented by general formula (1)> The magnetic paste contains, as component (B), a liquid epoxy resin (B) represented by general formula (1). [ka] (In general formula (1), R represents a hydrogen atom or a methyl group.)
[0030] By including component (B), the magnetic paste can have a lower viscosity, which improves the productivity of the inductor substrate and also improves the mechanical strength of the cured product.
[0031] The epoxy resin represented by the general formula (1) is liquid at a temperature of 25° C. in order to reduce the viscosity of the magnetic paste.
[0032] In the general formula (1), R represents a hydrogen atom or a methyl group, and from the viewpoint of obtaining the effects of the present invention remarkably, a methyl group is preferable. In particular, when R is a methyl group, not only can the viscosity of the magnetic paste be effectively reduced, but also, surprisingly, the relative permeability and magnetic loss of the cured product of the magnetic paste can be effectively improved.
[0033] The bonding position of R in the general formula (1) is preferably the ortho position relative to the position where the benzene ring is bonded to the nitrogen atom.
[0034] The liquid epoxy resin represented by the general formula (1) is preferably a liquid epoxy resin represented by the general formula (2). [ka] (In general formula (2), R 1 is the same as R in general formula (1).
[0035] As the component (B), a commercially available product can be used. Examples of commercially available products include "ELM-100H" manufactured by Sumitomo Chemical Co., Ltd. and "630" manufactured by Mitsubishi Chemical Corporation. As the component (B), one type may be used alone, or two or more types may be used in combination.
[0036] The epoxy equivalent of the (B) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 90 g / eq. to 1000 g / eq. Within this range, the crosslink density of the cured product is sufficient, and a magnetic layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236 and is the mass of a resin containing one equivalent of an epoxy group.
[0037] The weight average molecular weight of component (B) is preferably 100 to 5000, more preferably 150 to 3000, and even more preferably 250 to 1500. Here, the weight average molecular weight of component (B) is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0038] From the viewpoint of obtaining a magnetic layer exhibiting good mechanical strength, the content of component (B) is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, when the non-volatile components in the magnetic paste are taken as 100% by mass. The upper limit of the content of component (B) is not particularly limited as long as the effects of the present invention are achieved, but is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0039] The content (volume %) of component (B) is preferably 1 volume % or more, more preferably 3 volume % or more, and even more preferably 5 volume % or more, assuming that the non-volatile components in the magnetic paste are 100 volume %. The upper limit is not particularly limited as long as the effects of the present invention are achieved, but is preferably 25 volume % or less, more preferably 20 volume % or less, and even more preferably 15 volume % or less.
[0040] <(C) Dispersant> The magnetic paste may contain, as an optional component, (C) a dispersant.
[0041] Examples of the (C) dispersant include phosphate ester-based dispersants such as polyoxyethylene alkyl ether phosphate; anionic dispersants such as sodium dodecyl benzyl sulfonate, sodium laurate, and ammonium salts of polyoxyethylene alkyl ether sulfate; and nonionic dispersants such as organosiloxane-based dispersants, acetylene glycol, polyoxyethylene alkyl ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene alkyl phenyl ether, polyoxyethylene alkyl amine, and polyoxyethylene alkyl amide. Among these, anionic dispersants are preferred. Dispersants may be used alone or in combination of two or more.
[0042] The phosphate ester-based dispersant may be a commercially available product, such as "RS-410," "RS-610," or "RS-710" from the "Phosphanol" series manufactured by Toho Chemical Industry Co., Ltd.
[0043] Examples of commercially available organosiloxane-based dispersants include "BYK347" and "BYK348" manufactured by BYK-Chemie.
[0044] Commercially available polyoxyalkylene dispersants include "AKM-0531", "AFB-1521", "SC-0505K", "SC-1015F", "SC-0708A", and "HKM-50A" from the "Marialim" series manufactured by NOF Corporation.
[0045] Commercially available acetylene glycols include the "Surfynol" series manufactured by Air Products and Chemicals Inc., such as "82", "104", "440", "465", and "485", as well as "Olefin Y".
[0046] In order to prominently exhibit the effects of the present invention, the content of the dispersant (C) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, based on 100% by mass of the non-volatile components in the magnetic paste, and the upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.
[0047] <(D) Hardener> The magnetic paste may contain a hardener (D) as an optional component. The hardener (D) includes an epoxy resin hardener having the function of hardening the component (B) and a hardening accelerator having the function of accelerating the hardening rate of the component (B). The magnetic paste preferably contains a hardening accelerator as the hardener (D).
[0048] -Epoxy resin hardener- The epoxy resin curing agent can usually react with the epoxy resin to cure the magnetic paste. Examples of the epoxy resin curing agent include phenol-based epoxy resin curing agents, naphthol-based epoxy resin curing agents, active ester-based epoxy resin curing agents, acid anhydride-based epoxy resin curing agents, benzoxazine-based epoxy resin curing agents, cyanate ester-based epoxy resin curing agents, and imidazole-based epoxy resin curing agents. As the epoxy resin curing agent, from the viewpoint of reducing the viscosity of the magnetic paste, acid anhydride-based epoxy resin curing agents and imidazole-based epoxy resin curing agents are preferred, and from the viewpoint of the mechanical strength of the cured product obtained, imidazole-based epoxy resin curing agents are more preferred. The epoxy resin curing agent may be used alone or in combination of two or more types.
[0049] As the phenol-based epoxy resin curing agent and naphthol-based epoxy resin curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based epoxy resin curing agent having a novolac structure or a naphthol-based epoxy resin curing agent having a novolac structure is preferred. As the phenol-based epoxy resin curing agent, a nitrogen-containing phenol-based epoxy resin curing agent is preferred, a triazine skeleton-containing phenol-based epoxy resin curing agent is more preferred, and a triazine skeleton-containing phenol novolac epoxy resin curing agent is even more preferred.
[0050] Specific examples of phenol-based epoxy resin curing agents and naphthol-based epoxy resin curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by DIC Corporation, and "GDP-6115L" and "GDP-6115H" manufactured by Gun-ei Chemical Co., Ltd.
[0051] The active ester epoxy resin curing agent is not particularly limited, but generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester epoxy resin curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester epoxy resin curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester epoxy resin curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0052] Specifically, active ester-based epoxy resin curing agents containing a dicyclopentadiene-type diphenol structure, active ester-based epoxy resin curing agents containing a naphthalene structure, active ester-based epoxy resin curing agents containing an acetylated product of phenol novolac, and active ester-based epoxy resin curing agents containing a benzoylated product of phenol novolac are preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structure consisting of phenylene-dicyclopentylene-phenylene.
[0053] Commercially available active ester epoxy resin curing agents include DIC Corporation's "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" as active ester epoxy resin curing agents containing a dicyclopentadiene-type diphenol structure; DIC Corporation's "EXB9416-70BK" as an active ester compound containing a naphthalene structure; Mitsubishi Chemical Corporation's "DC808" as an active ester epoxy resin curing agent containing an acetylated product of phenol novolac; Mitsubishi Chemical Corporation's "YLH1026", "YLH1030", and "YLH1048" as active ester epoxy resin curing agents containing a benzoylated product of phenol novolac; and Mitsubishi Chemical Corporation's "DC808" as an active ester epoxy resin curing agent which is an acetylated product of phenol novolac.
[0054] Examples of the acid anhydride epoxy resin curing agent include epoxy resin curing agents having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride epoxy resin curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarbo Examples of such anhydrides include carboxylic acid dianhydride, biphenyltetracarboxylic acid dianhydride, naphthalenetetracarboxylic acid dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid.
[0055] Commercially available acid anhydride-based epoxy resin curing agents include "HNA-100" and "MH-700" manufactured by New Japan Chemical Co., Ltd.
[0056] Specific examples of benzoxazine-based epoxy resin curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0057] Examples of the cyanate ester-based epoxy resin curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based epoxy resin curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which a portion or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan Ltd.
[0058] Examples of imidazole-based epoxy resin curing agents include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-phenylimidazo 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2- Examples of the imidazole compound include phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds with epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.
[0059] As the imidazole-based epoxy resin curing agent, a commercially available product may be used, for example, "2MZA-PW" and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0060] The ratio of the amount of epoxy resin to the epoxy resin curing agent is preferably in the range of 1:0.2 to 1:2, more preferably in the range of 1:0.3 to 1:1.5, and even more preferably in the range of 1:0.4 to 1:1. Here, the reactive group of the epoxy resin curing agent is an active hydroxyl group, an active ester group, etc., and varies depending on the type of the epoxy resin curing agent. The total number of epoxy groups of the epoxy resin is the value obtained by dividing the mass of the non-volatile component of each epoxy resin by the epoxy equivalent, and the total number of reactive groups of the epoxy resin curing agent is the value obtained by dividing the mass of the non-volatile component of each epoxy resin curing agent by the reactive group ...
[0061] -Curing accelerator- The curing accelerator usually acts as a catalyst in the curing reaction of the epoxy resin, and can accelerate the curing reaction. Examples of the curing accelerator include amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. From the viewpoint of reducing the viscosity of the magnetic paste, the curing accelerator is preferably an amine-based curing accelerator, an imidazole-based curing accelerator, and a guanidine-based curing accelerator, and more preferably an imidazole-based curing accelerator from the viewpoint of improving the mechanical strength of the obtained cured product. The curing accelerator may be used alone or in combination of two or more kinds.
[0062] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0063] As the amine-based curing accelerator, commercially available products may be used, for example, "PN-50", "PN-23", "MY-25" and the like manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0064] The imidazole-based curing accelerator is the same as the imidazole-based epoxy resin curing agent described above. When the imidazole-based epoxy resin curing agent is used in combination with other epoxy resin curing agents, it may function as a curing accelerator.
[0065] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.
[0066] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.
[0067] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0068] (D) The content of the hardener is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, when the non-volatile components in the magnetic paste are taken as 100% by mass, from the viewpoint of reducing the viscosity of the magnetic paste, and the upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, when the resin components in the magnetic paste are taken as 100% by mass.
[0069] <(E) Other Additives> The magnetic paste may further contain (E) other additives as necessary. Examples of such other additives include hardening retarders such as triethyl borate; inorganic fillers (excluding those corresponding to magnetic powder); thermosetting resins (excluding those corresponding to components (B) and (D)); thermoplastic resins; flame retardants; organic fillers; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; and resin additives such as thickeners; defoamers; leveling agents; adhesion promoters; and colorants.
[0070] The content of the organic solvent contained in the magnetic paste described above is preferably less than 1.0% by mass, more preferably 0.8% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, based on the total mass of the magnetic paste. There is no particular lower limit, but the lower limit is 0.001% by mass or more, or no organic solvent is contained. Even if the magnetic paste does not contain an organic solvent, the viscosity of the magnetic paste can be reduced because it contains component (B). The small amount of organic solvent in the magnetic paste can suppress the generation of voids due to the evaporation of the organic solvent.
[0071] <Magnetic paste manufacturing method> The magnetic paste can be produced, for example, by a method in which the ingredients are mixed together using a mixing device such as a three-roll mixer or a rotary mixer.
[0072] <Properties of magnetic paste> The magnetic paste exhibits the characteristic of low viscosity. Therefore, the magnetic paste has excellent productivity for inductor substrates. The viscosity at 25°C is preferably 600 Pa·s or less, more preferably 550 Pa·s or less, even more preferably 500 Pa·s or less, 400 Pa·s or less, or 300 Pa·s or less, and is preferably 30 Pa·s or more, preferably 50 Pa·s or more, and more preferably 60 Pa·s or more. The viscosity can be measured, for example, using an E-type viscometer (RE-80U manufactured by Toki Sangyo Co., Ltd.), and details can be measured by the method described in the examples below.
[0073] The cured product obtained by heating the magnetic paste at 190°C for 90 minutes exhibits the characteristic of having a high relative magnetic permeability at a frequency of 10 MHz. Thus, the cured product provides a magnetic layer with a high relative magnetic permeability. The relative magnetic permeability of this cured product at a frequency of 10 MHz is preferably 5 or more, more preferably 10 or more, and even more preferably 15 or more. The upper limit is not particularly limited, but may be 50 or less. The relative magnetic permeability can be measured by the method described in the examples below.
[0074] A cured product obtained by heating the magnetic paste at 190°C for 90 minutes usually exhibits the property of low magnetic loss at a frequency of 10 MHz. Thus, the cured product provides a magnetic layer with low magnetic loss. The magnetic loss of this cured product at a frequency of 10 MHz is preferably 0.1 or less, more preferably 0.09 or less, and even more preferably 0.08 or less. The lower limit is not particularly limited, but may be 0.001 or more. The magnetic loss can be measured by the method described in the examples below.
[0075] A cured product obtained by heating the magnetic paste at 190°C for 90 minutes usually exhibits excellent mechanical strength (maximum point strength). Thus, the cured product provides a magnetic layer with excellent maximum point strength. The maximum point strength is preferably 10 MPa or more, more preferably 20 MPa or more, and even more preferably 30 MPa or more. There is no particular upper limit, but it may be 100 MPa or less. The maximum point strength can be measured by the method described in the examples below.
[0076] The cured product obtained by heating the magnetic paste at 190°C for 90 minutes usually exhibits elongation properties. The elongation is preferably 0.001% or more, more preferably 0.01% or less, and even more preferably 0.1% or more. There is no particular upper limit. The elongation can be measured by the method described in the examples below.
[0077] [Circuit boards and manufacturing methods for circuit boards] The circuit board of the present invention includes a magnetic layer formed from a cured product of a magnetic paste. The circuit board is produced, for example, by a production method including the following step (A). (A) A process of supplying a magnetic paste onto an inner layer substrate and molding the magnetic paste using a compression mold to form a magnetic layer.
[0078] Moreover, the circuit board preferably includes the following steps (B) to (D) in addition to the step (A). (B) a step of drilling holes in the magnetic layer; (C) a step of roughening the surface of the magnetic layer; and (D) A step of forming a conductive layer on the polished surface of the magnetic layer. The above steps (A) to (D) for manufacturing the circuit board will now be described in detail.
[0079] <Process (A)> Step (A) is a step of supplying a magnetic paste onto an inner layer substrate, and molding the magnetic paste by compression molding to form a magnetic layer. In one embodiment of step (A), the magnetic paste is supplied onto the inner layer substrate, and the supplied magnetic paste is pressurized in a mold such as a metal die, heated as necessary, and compression molded. After compression molding, the magnetic paste is thermally cured as necessary to form a magnetic layer.
[0080] An insulating substrate can be used as the inner layer substrate. Examples of materials for the inner layer substrate include insulating base materials such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The inner layer substrate may be an inner layer circuit substrate having wiring and the like built into its thickness.
[0081] 1, the inner layer substrate 200 has a first conductor layer 420 provided on the first main surface 200a. The first conductor layer 420 may include a plurality of wirings. In the illustrated example, only the wirings constituting the coil-shaped conductive structure 400 of the inductor element are shown.
[0082] Examples of the material of the first conductor layer 420 include single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium; and alloys of two or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among them, from the viewpoints of versatility, cost, ease of patterning, and the like, it is preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy, and it is more preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, and it is even more preferable to use copper. Examples of the method of forming the first conductor layer 420 include a plating method, a sputtering method, and a vapor deposition method, and among them, a plating method is preferable. In a preferred embodiment, the surface of the cured product is plated by an appropriate method such as a semi-additive method or a full-additive method to form a patterned conductor layer having a desired wiring pattern.
[0083] The first conductor layer 420 may have a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. The thickness of the first conductor layer 420 is the same as that of the second conductor layer 440 described later.
[0084] 2, after preparing the inner layer substrate 200, the magnetic paste is molded using a compression mold to form the first magnetic layer 320 on the inner layer substrate 200. The specific operation of the compression mold usually includes supplying the magnetic paste (not shown) onto the inner layer substrate 200 and compressing and molding the magnetic paste using a mold such as a metal die. After molding the magnetic paste, it is usually subjected to thermal curing in the mold, as described below.
[0085] A specific operation of compression molding may be, for example, as follows. An upper mold and a lower mold are prepared as molds for compression molding. An inner layer substrate is placed in the lower mold, and magnetic paste is placed on the inner layer substrate. The placed inner layer substrate may be fixed to the lower mold by vacuum adsorption. Also, the magnetic paste may be placed on the inner layer substrate before placing the inner layer substrate on the lower mold, or may be placed on the inner layer substrate after placing the inner layer substrate on the lower mold. Then, the upper mold and the lower mold are clamped so that the upper mold is in contact with the magnetic paste, and heat and pressure are applied to perform molding.
[0086] The specific operation of the compression mold may be, for example, as follows: An inner layer substrate is placed in the upper mold. The placed inner layer substrate may be fixed to the upper mold by vacuum suction. A magnetic paste is placed on the lower mold. The upper and lower molds are then clamped together so that the magnetic paste placed on the lower mold is in contact with the inner layer base material attached to the upper mold, and heat and pressure are applied to perform molding.
[0087] The compression molding conditions vary depending on the composition of the magnetic paste. The pressure applied during molding is preferably 1 MPa or more, more preferably 3 MPa or more, and even more preferably 5 MPa or more, and is preferably 50 MPa or less, more preferably 30 MPa or less, and even more preferably 20 MPa or less. The pressure application time is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 5 minutes or more, and is preferably 60 minutes or less, more preferably 30 minutes or less, and even more preferably 20 minutes or less.
[0088] In order to ensure moldability, the compression mold may be heated as necessary while pressing the material, preferably to a temperature of 80° C. or higher, more preferably 100° C. or higher, and even more preferably 120° C. or higher, and preferably to a temperature of 220° C. or lower, more preferably 200° C. or lower, and even more preferably to a temperature of 170° C. or lower.
[0089] After the magnetic paste is molded on the inner layer substrate by compression molding, the magnetic paste is thermally cured to form the first magnetic layer 320, as shown in an example in Fig. 2. The thermal curing conditions for the magnetic paste vary depending on the type of magnetic paste, but the curing temperature is usually in the range of 120°C to 240°C (preferably in the range of 150°C to 220°C, more preferably in the range of 170°C to 210°C), and the curing time is in the range of 5 minutes to 120 minutes (preferably in the range of 10 minutes to 100 minutes, more preferably in the range of 15 minutes to 100 minutes).
[0090] Before the molded magnetic paste is thermally cured, the magnetic paste may be subjected to a preheating treatment in which the magnetic paste is heated at a temperature lower than the curing temperature. For example, prior to thermally curing the magnetic paste, the resin composition layer may be preheated for usually 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes) at a temperature of usually 50°C or more and less than 120°C (preferably 60°C or more and 115°C or less, more preferably 70°C or more and 110°C or less).
[0091] After forming the magnetic layer, a plurality of through holes 220 may be formed penetrating the inner layer substrate 200 so as to reach the second main surface 200b from the first main surface 200a of the inner layer substrate 200, as shown in an example in Fig. 3. The through holes 220 may be formed using, for example, a drill, a laser, plasma, or the like. The dimensions and shape of the through holes may be appropriately determined depending on the design of the printed wiring board.
[0092] Through-hole wiring 220a may be formed in through-hole 220. Through-hole wiring 220a may be formed by a method such as plating, sputtering, or vapor deposition. Usually, an external terminal 240 is formed on inner layer substrate 200 before or after forming through-hole wiring 220a, or simultaneously with forming through-hole wiring 220a. Through-hole wiring 220a may electrically connect first conductor layer 420 and external terminal 240.
[0093] The line (L) / space (S) ratio of the first conductor layer 420 and the external terminal 240 is not particularly limited, but from the viewpoint of obtaining a magnetic layer with excellent smoothness by reducing surface irregularities, it is usually 900 / 900 μm or less, preferably 700 / 700 μm or less, more preferably 500 / 500 μm or less, even more preferably 300 / 300 μm or less, and even more preferably 200 / 200 μm or less. The lower limit of the line / space ratio is not particularly limited, but from the viewpoint of improving the embedding of the magnetic layer in the space, it is preferably 1 / 1 μm or more.
[0094] <Process (B)> In step (B), as shown in FIG. 4, the first magnetic layer 320 is drilled to form a via hole 360. The via hole 360 serves as a path for electrically connecting the first conductor layer 420 and a second conductor layer 440 described below. The via hole 360 may be formed using, for example, a drill, a laser, plasma, or the like, depending on the composition of the magnetic paste used to form the magnetic layer. The size and shape of the via hole may be appropriately determined depending on the design of the circuit board.
[0095] <Process (C)> In step (C), the surface of the magnetic layer in which the via holes are formed is roughened. The procedure and conditions of the roughening step are not particularly limited, and known procedures and conditions that are usually used in the manufacturing method of a multilayer printed wiring board can be adopted. As the roughening step, for example, the first magnetic layer 32 can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0096] The swelling liquid that can be used in the roughening step is not particularly limited, but includes an alkaline solution, a surfactant solution, and the like, and is preferably an alkaline solution. As the alkaline solution that is the swelling liquid, a sodium hydroxide solution and a potassium hydroxide solution are more preferable. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan.
[0097] The swelling treatment using a swelling liquid is not particularly limited, but can be carried out, for example, by immersing the inner layer substrate 200 provided with the first magnetic layer 320 for 1 to 20 minutes in a swelling liquid at 30° C. to 90° C. From the viewpoint of suppressing swelling of the resin constituting the first magnetic layer 32 to an appropriate level, it is preferable to immerse the first magnetic layer 32 in a swelling liquid at 40° C. to 80° C. for 5 to 15 minutes.
[0098] The oxidizing agent that can be used in the roughening treatment with an oxidizing agent is not particularly limited, and examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment with an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the first magnetic layer 32 in an oxidizing agent solution heated to 60°C to 80°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact P" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0099] The neutralizing solution that can be used in the neutralization treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigans P" manufactured by Atotech Japan. The neutralization treatment using a neutralizing solution can be performed by immersing the treated surface that has been roughened with an oxidizing solution in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method of immersing the first magnetic layer 320 that has been roughened with an oxidizing solution in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferable.
[0100] The arithmetic mean roughness (Ra) of the magnetic layer after roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0101] In step (C), polishing may be carried out instead of the roughening treatment to remove protruding or adhering excess magnetic layer and to flatten the surface.
[0102] <Process (D)> In step (D), a second conductor layer 440 is formed on the first magnetic layer 320, as shown in an example in FIG.
[0103] The conductive material that can form the second conductive layer 440 is similar to the material of the first conductive layer described in step (A).
[0104] From the viewpoint of thinning, the thickness of the second conductor layer 440 is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0105] The second conductor layer 440 can be formed by plating. The second conductor layer 440 is preferably formed by a wet plating method such as a semi-additive method or a full-additive method including an electroless plating process, a mask pattern forming process, an electrolytic plating process, and a flash etching process. By forming the second conductor layer 440 using a wet plating method, it is possible to form the second conductor layer 440 including a desired wiring pattern. Note that this process also forms an in-via-hole wiring 360a in the via hole 360.
[0106] The first conductor layer 420 and the second conductor layer 440 may be provided in a spiral shape, for example, as shown in Figs. 6 to 8 described later. In one example, one end of the spiral wiring part of the second conductor layer 440 on the center side is electrically connected to one end of the spiral wiring part of the first conductor layer 420 on the center side by the via-hole wiring 360a. The other end of the spiral wiring part of the second conductor layer 440 on the outer periphery side is electrically connected to the land 420a of the first conductor layer 42 by the via-hole wiring 360a. Therefore, the other end of the spiral wiring part of the second conductor layer 440 on the outer periphery side is electrically connected to the external terminal 240 via the via-hole wiring 360a, the land 420a, and the through-hole wiring 220a.
[0107] The coil-shaped conductive structure 400 is composed of a spiral wiring portion that is a part of the first conductor layer 420, a spiral wiring portion that is a part of the second conductor layer 440, and via-hole wiring 360a that electrically connects the spiral wiring portion of the first conductor layer 420 and the spiral wiring portion of the second conductor layer 440.
[0108] After step (D), a step of forming a magnetic layer on the conductor layer may be performed. In detail, as shown in an example in Fig. 7, a second magnetic layer 340 is formed on the first magnetic layer 320 on which the second conductor layer 440 and the via-hole wiring 360a are formed. The second magnetic layer may be formed by the same steps as those already described.
[0109] [Inductor board] The inductor substrate includes the circuit substrate of the present invention. When the inductor substrate includes a circuit substrate obtained by the method for manufacturing a circuit substrate of the present invention, the inductor substrate has a magnetic layer and a conductive structure at least partially embedded in the magnetic layer, and includes an inductor element formed by the conductive structure and a part of the magnetic layer that extends in the thickness direction of the magnetic layer and is surrounded by the conductive structure. Here, FIG. 6 is a schematic plan view of the inductor substrate having an inductor element therein, as viewed from one side in the thickness direction. FIG. 7 is a schematic view showing a cut end surface of the inductor substrate cut at the position indicated by the dashed line II-II in FIG. 6. FIG. 8 is a schematic plan view for explaining the configuration of a first conductive layer of the inductor substrate.
[0110] 6 and 7, the inductor substrate 100 is a build-up wiring board having a plurality of magnetic layers (first magnetic layer 320, second magnetic layer 340) and a plurality of conductor layers (first conductor layer 420, second conductor layer 440), i.e., a build-up magnetic layer and a build-up conductor layer. The inductor substrate 100 also includes an inner layer substrate 200.
[0111] 7, the first magnetic layer 320 and the second magnetic layer 340 constitute the magnetic part 300 which can be seen as an integrated magnetic layer. Therefore, the coiled conductive structure 400 is provided so that at least a portion thereof is embedded in the magnetic part 300. That is, in the inductor substrate 100 of this embodiment, the inductor element is constituted by the coiled conductive structure 400 and a core portion which is a portion of the magnetic part 300 that extends in the thickness direction of the magnetic part 300 and is surrounded by the coiled conductive structure 400.
[0112] 8, the first conductor layer 420 includes a spiral wiring portion for constituting the coil-shaped conductive structure 400, and a rectangular land 420a electrically connected to the through-hole wiring 220a. In the illustrated example, the spiral wiring portion includes a straight portion, a bent portion bent at a right angle, and a detour portion that detours around the land 420a. In the illustrated example, the spiral wiring portion of the first conductor layer 420 has an overall outline that is substantially rectangular, and has a shape that winds counterclockwise from the center toward the outside.
[0113] Similarly, a second conductor layer 440 is provided on the first magnetic layer 320. The second conductor layer 440 includes a spiral wiring portion for configuring the coil-shaped conductive structure 400. In Fig. 6 or 7, the spiral wiring portion includes a straight portion and a bent portion bent at a right angle. In Fig. 6 or 7, the spiral wiring portion of the second conductor layer 44 has an overall outline that is substantially rectangular, and has a shape that is wound clockwise from the center toward the outside.
[0114] Such an inductor substrate can be used as a wiring board for mounting electronic components such as semiconductor chips, and can also be used as a (multilayer) printed wiring board using such a wiring board as an inner layer substrate.Furthermore, such a wiring board can be used as a chip inductor substrate obtained by dividing it into individual pieces, and can also be used as a surface-mounted printed wiring board.
[0115] In addition, various types of semiconductor devices can be manufactured using such a wiring board. The semiconductor device including such a wiring board can be suitably used in electric products (e.g., computers, mobile phones, digital cameras, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES
[0116] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the terms "parts" and "%" used to express amounts refer to "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0117] <Example 1> Epoxy resin (ELM-100H, amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) 4 parts by mass, dispersant (RS-710, phosphate ester-based dispersant, manufactured by Toho Chemical Co., Ltd.) 0.5 parts by mass, hardening accelerator (2P4MZ, imidazole-based hardening accelerator, manufactured by Shikoku Kasei Co., Ltd.) 0.25 parts by mass, magnetic powder (KUAMET NC1, Fe-based nanocrystalline magnetic material, D 50 : 25 μm, Epson Atmix) 58 parts by mass, magnetic powder ("AW02-08PF3F", Fe-based amorphous magnetic material, D 50 24 parts by mass of epoxy resin "ELM-100H" (3 μm, manufactured by Epson Atmix) were mixed and uniformly dispersed using a triple roll to prepare magnetic paste 1. The structural formula of the epoxy resin "ELM-100H" is shown below. [ka]
[0118] <Example 2> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("630", amine-based epoxy resin, manufactured by Mitsubishi Chemical Co., Ltd.). Apart from the above, magnetic paste 2 was prepared in the same manner as in Example 1. The structural formula of the epoxy resin "630" is shown below. [ka]
[0119] <Comparative Example 1> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("EP-3980S", amine-based epoxy resin, manufactured by ADEKA Corporation). Magnetic paste 3 was prepared in the same manner as in Example 1 except for the above. The structural formula of the epoxy resin "EP3980S" is shown below. [ka]
[0120] <Comparative Example 2> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("604", amine-based epoxy resin, manufactured by Mitsubishi Chemical Co., Ltd.). Apart from the above, magnetic paste 4 was prepared in the same manner as in Example 1. The structural formula of the epoxy resin "604" is shown below. [ka]
[0121] <Comparative Example 3> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", an amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("EX201IM", a phenyl-based epoxy resin, manufactured by Nagase ChemteX Corporation). Apart from the above, magnetic paste 5 was prepared in the same manner as in Example 1. The structural formula of the epoxy resin "EX201IM" is shown below. [ka]
[0122] <Comparative Example 4> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("828", bisphenol A-type epoxy resin, manufactured by Mitsubishi Chemical Co., Ltd.). Apart from the above, a magnetic paste 6 was prepared in the same manner as in Example 1. The structural formula of the epoxy resin "828" is shown below. [ka]
[0123] <Comparative Example 5> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", an amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("ED-523", a bifunctional dilutable epoxy resin, manufactured by ADEKA Corporation). Magnetic paste 7 was prepared in the same manner as in Example 1 except for the above. The structural formula of the epoxy resin "ED-523" is shown below. [ka]
[0124] <Comparative Example 6> In Example 1, 4 parts by mass of the epoxy resin ("ELM-100H", an amine-based epoxy resin, manufactured by Sumitomo Chemical Co., Ltd.) was changed to 4 parts by mass of an epoxy resin ("YX4000HK", a biphenyl-type epoxy resin, manufactured by Mitsubishi Chemical Co., Ltd.). Apart from the above, a magnetic paste 8 was prepared in the same manner as in Example 1. The structural formula of the epoxy resin "YX4000HK" is shown below. [ka]
[0125] <Viscosity measurement> The temperature of the magnetic pastes 1 to 8 was kept at 25±2° C., and the viscosity at 25° C. was measured using an E-type viscometer (Toki Sangyo Co., Ltd. "RE-80U", 3°×R9.7 cone, rotation speed 0.5 rpm).
[0126] <Measurement of relative permeability and magnetic loss> As a support, a polyethylene terephthalate (PET) film ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) treated with a silicone-based release agent was prepared. The magnetic pastes 1 to 8 prepared in each Example and Comparative Example were uniformly applied to the release surface of the PET film with a doctor blade so that the paste layer after drying had a thickness of 100 μm, to obtain a resin sheet. The obtained resin sheet was heated at 190° C. for 90 minutes to thermally cure the paste layer, and the support was peeled off to obtain a sheet-like cured product. The obtained cured product was cut into a test piece with a width of 5 mm and a length of 18 mm to be used as an evaluation sample. The evaluation sample was measured for relative permeability (μ') and magnetic loss (μ'') at a measurement frequency of 10 MHz at room temperature of 23° C. using an Agilent Technologies ("HP8362B" manufactured by Agilent Technologies) by a 3-turn coil method with a measurement frequency of 10 MHz, and the loss factor was obtained. The loss factor was calculated from the following formula. tan δ=μ' / μ''
[0127] <Measurement of maximum strength and elongation> As a support, a polyethylene terephthalate (PET) film ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) treated with a silicone-based release agent was prepared. The magnetic pastes 1 to 8 prepared in each Example and Comparative Example were uniformly applied to the release surface of the PET film with a doctor blade so that the paste layer after drying had a thickness of 100 μm, to obtain a resin sheet. The obtained resin sheet was heated at 190°C for 90 minutes to thermally cure the paste layer, and the support was peeled off to obtain a sheet-like cured product. The obtained cured product was subjected to a tensile test using a Tensilon universal testing machine (manufactured by A&D Co., Ltd.) in accordance with the Japanese Industrial Standards (JIS K7127), and the maximum strength and elongation were measured.
[0128] [Table 1]
[0129] It was found that Examples 1 and 2, which contain component (B), have superior magnetic properties and good maximum strength and elongation compared to Comparative Examples 1 to 6, which do not contain component (B).In addition, it was found that the low viscosity of the composition results in excellent workability for producing an inductor substrate.
[0130] In Comparative Example 1, which used a component similar to the (B) component, the cured product was brittle, so the magnetic properties and mechanical properties could not be measured. In Comparative Example 2, which used a component similar to the (B) component, the product did not become a paste, so the magnetic properties, viscosity, and mechanical properties could not be measured. In Comparative Example 4, which used an epoxy resin having a bisphenol A skeleton, the viscosity was too high and the viscosity could not be measured. In Comparative Example 5, which used an epoxy resin with a low viscosity, the cured product was brittle, so the magnetic properties and mechanical properties could not be measured. In Comparative Example 6, which used a solid epoxy resin (an epoxy resin that is solid at a temperature of 25°C), the product did not become a paste, so the magnetic properties, viscosity, and mechanical properties could not be measured. [Explanation of symbols]
[0131] 100 Inductor Board 200 Inner layer board 200a 1st main surface 200b 2nd main surface 220 through hole 220a Through hole wiring 240 External terminal 300 Magnetic part 310 Magnetic Sheet 320a Resin composition layer 320 First insulating layer 330 Support 340 Second insulating layer 360 Beer Hall 360a via hole wiring 400 Coil-shaped conductive structure 420 First conductor layer 420a Land 440 Second conductor layer
Claims
[Claim 1] (A) magnetic powder, (B) a liquid epoxy resin represented by the following general formula (1), and (C) a dispersant; and a magnetic paste for forming an inductor substrate using a compression mold, comprising: (A) A magnetic paste having a magnetic powder content of 70% by mass or more, assuming that the non-volatile components in the magnetic paste are 100% by mass. 【Chemistry 1】 (In general formula (1), R represents a hydrogen atom or a methyl group.)
Citation Information
Patent Citations
Resin composition
JP2019014843A
Resin composition, sheet-like laminated material, printed wiring board, and semiconductor device
JP2019210319A
Inductor and method of manufacturing the same
JP2020038940A
Resin composition
WO2018194099A1
Electronic circuit package
JP2017199896A